Method for recycling waste hydrogenation catalyst

Through simplified recycling steps, molybdenum is extracted using chlorine and sonication technology, and combined with ammonium bicarbonate heat treatment to form an alumina-based support, solving the problems of low recycling rate and short catalyst activity in the prior art, and a high-activity and long-life hydrogenation catalyst is prepared.

CN119819377AActive Publication Date: 2025-04-15CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202311316972.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-12
Publication Date
2025-04-15
Estimated Expiration
2043-10-12

AI Technical Summary

Technical Problem

The existing hydrogenation catalyst recovery and reuse methods have problems such as complex process steps, low recycling rate of active metals and/or support, and low activity and short life of the prepared catalyst.

Method used

By extracting and crushing the molybdenum-nickel-based waste catalyst, reacting with chlorine, ultrasonic treatment in anhydrous organic solvent, then mixing it with ammonium bicarbonate solution for sealing and heat treatment, forming an alumina-based support, and loading the impregnation liquid onto the support, a hydrogenation catalyst with high activity and long life is prepared.

Benefits of technology

The recovery step is simplified, and the metal components and alumina support in the waste catalyst are efficiently utilized. The new catalyst prepared has high activity and long life, which improves the efficiency of residual oil hydrogenation reaction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004489647800000081
    Figure BDA0004489647800000081
  • Figure BDA0004489647800000082
    Figure BDA0004489647800000082
Patent Text Reader

Abstract

The invention discloses a method for recycling a waste hydrogenation catalyst. The method comprises the following steps: (1) crushing a solid obtained after extraction and oil removal of the molybdenum-nickel waste catalyst; (2) reacting the catalyst powder with chlorine, cooling, transferring into an anhydrous organic solvent for ultrasonic treatment, and separating to obtain a solvent I and a material II; (3) mixing the material II with an ammonium bicarbonate solution, then carrying out sealed heat treatment, molding the treated material, drying, and roasting in an inert gas atmosphere to prepare an alumina-based carrier; (4) dropwise adding a solvent I into a solution containing a nickel source, a phosphorus source and a complexing agent to obtain an impregnation liquid; and (5) impregnating the impregnation liquid obtained in the step (4) into an alumina-based carrier, and then curing and drying to obtain the hydrogenation catalyst. The method has the advantages that the recovery steps are simple, the metal components and the alumina carrier of the nickel-molybdenum waste catalyst can be efficiently utilized, and the prepared new catalyst is applied to the residual oil hydrogenation reaction and has the characteristics of high activity and long service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of recycling of waste hydrogenation catalysts, and in particular relates to a method for recycling waste hydrogenation catalysts. Background Art

[0002] The amount of hydrogenation catalyst used is large and it is not easy to regenerate, resulting in a low metal recycling rate and a waste of resources. At present, the basic life of residual oil hydrogenation catalyst is 8,000 hours. Each residual oil hydrogenation unit produces hundreds of tons of waste catalysts each year. China currently has more than a dozen residual oil hydrogenation units, and the annual residual oil waste catalyst can reach tens of thousands of tons. The catalyst recycling companies are currently mainly considering the recovery of molybdenum and nickel active metals in residual oil hydrogenation catalysts. The alumina carrier is basically used as waste slag for cement or ceramic companies, and the carrier utilization rate is too low. The recycling and reuse of active metals and alumina carriers has become an important direction of current hydrogenation catalyst research.

[0003] CN108067272A discloses a method for preparing a hydrogenation catalyst. The method comprises: (1) extracting, microwave treating and crushing molybdenum-nickel waste hydrogenation catalyst; (2) uniformly mixing the catalyst powder crushed in step (1) with alkali and calcining at high temperature; (3) soaking the waste catalyst after calcination in step (2) in hot water; (4) reacting the filtrate in step (3) with an acidic solution to prepare pseudo-boehmite, kneading, shaping and calcining the pseudo-boehmite to obtain a carrier; (5) adding Na to the solution filtered in step (4); 2 S solution to obtain MoO 3 ; (6) adding acid to the solid after filtration in step (3), then using alkaline solution to remove Fe and Al in the solution, and finally preparing basic nickel carbonate; (7) preparing molybdenum-nickel-phosphorus solution with molybdenum oxide in step (5) and basic nickel carbonate in step (6), impregnating the carrier in step (4), and preparing hydrogenation catalyst after drying and roasting. This method is suitable for recycling waste molybdenum-nickel catalyst to prepare new catalyst, but the process of this method is too complicated, and there is a problem of low recovery rate of carrier and metal.

[0004] In summary, the existing methods for recycling and reusing hydrogenation catalysts have problems to varying degrees, such as complicated process steps, low recycling rate of active metals and / or carriers, and low activity and short life of the prepared catalysts. Therefore, further in-depth research on the recycling and utilization of spent hydrogenation catalysts is of great significance. Summary of the invention

[0005] In view of the shortcomings of the prior art, the present invention provides a method for recycling waste hydrogenation catalysts. The method of the present invention has simple recycling steps, can efficiently utilize the metal components and alumina carrier of nickel-molybdenum waste catalysts, and the prepared new catalyst is applied to residual oil hydrogenation reaction and has the characteristics of high activity and long life.

[0006] The present invention provides a method for recycling a waste hydrogenation catalyst, comprising the following steps:

[0007] (1) crushing the solid after extracting and removing oil from the molybdenum-nickel waste catalyst;

[0008] (2) After the catalyst powder reacts with chlorine, it is cooled and transferred to an anhydrous organic solvent for ultrasonic treatment to separate solvent I and material II;

[0009] (3) mixing material II with an ammonium bicarbonate solution and subjecting the mixture to sealed heat treatment, forming the treated material, drying it, and calcining it in an inert gas atmosphere to obtain an alumina-based carrier;

[0010] (4) adding solvent I dropwise to a solution containing a nickel source, a phosphorus source and a complexing agent to obtain an impregnation solution;

[0011] (5) The impregnation solution obtained in step (4) is impregnated into an alumina-based carrier, and then cured and dried to obtain a hydrogenation catalyst.

[0012] According to the present invention, the waste hydrogenation catalyst in step (1) is a nickel-molybdenum waste catalyst, that is, a molybdenum-nickel catalyst deactivated after residual oil hydrogenation treatment. The waste hydrogenation catalyst includes 70% to 90% of catalyst solids and 10% to 30% of petroleum fractions by weight. Further, the waste hydrogenation catalyst after extraction and deoiling, based on the catalyst mass and in terms of mass fraction, includes:

[0013] 10% to 25% molybdenum calculated as molybdenum trioxide;

[0014] 3% to 10% nickel, calculated as nickel oxide;

[0015] 3% to 10% vanadium, calculated as vanadium pentoxide;

[0016] 6% to 14% carbon;

[0017] 41% to 77% carrier alumina.

[0018] According to the present invention, the organic solvent used for extraction in step (1) includes one or more of toluene, petroleum ether, and ethanol; the extraction temperature is 80-110°C, and the extraction time is 60-90h. The mass ratio of organic solvent to catalyst is 25-50:1. The extraction is used to remove the petroleum fraction in the nickel-molybdenum waste catalyst.

[0019] According to the present invention, in step (1), the waste hydrogenation catalyst is extracted and then dried and crushed. The drying temperature is 120-200° C. and the drying time is 3-8 hours. The crushing is to crush the waste hydrogenation catalyst to a particle size of 200-500 mesh, preferably 300-400 mesh.

[0020] According to the present invention, the purity of the chlorine gas in step (2) is 96% or more by volume. The flow rate of the chlorine gas in step (2) is 2.7 to 6.8 mL / (min·g catalyst); the reaction conditions are as follows: the reaction temperature is 300 to 400° C., and the reaction time is 40 to 90 min.

[0021] According to the present invention, in step (2), the mixture is cooled to a temperature required for ultrasonic treatment. The anhydrous organic solvent is one or more selected from acetone, tetrahydrofuran, and acetic acid. The mass ratio of the anhydrous organic solvent to the catalyst powder is 3 to 5:1.

[0022] According to the present invention, the ultrasonic frequency in step (2) is 10KHz to 150KHz, the ultrasonic treatment temperature is 20°C to 70°C, and the treatment time is 0.5 to 2h.

[0023] According to the present invention, the mass ratio of the material II to the ammonium bicarbonate solution in step (3) is 1:4 to 1:7, and the mass concentration of the ammonium bicarbonate solution is 15% to 25%.

[0024] According to the present invention, the sealing heat treatment temperature described in step (3) is 120-160°C, and the treatment time is 4-8h. The heating rate to the heat treatment temperature is 5°C / min-20°C / min. Preferably, a sealing pretreatment is performed before the sealing heat treatment, the pretreatment temperature is 60-100°C, the constant temperature treatment time is 2-4h, the heating rate before the pretreatment is 10-20°C / min, and the heating rate after the pretreatment is 5-10°C / min, and the heating rate after the pretreatment is at least 3°C / min lower than that before the pretreatment, preferably at least 5°C / min lower. The heat treatment is generally performed in a high-pressure reactor.

[0025] According to the present invention, the kneading molding described in step (3) is carried out by conventional methods in the art. During the molding process, adhesives, extrusion aids and water can be added as needed. The adhesive can be at least one of nitric acid, acetic acid, and citric acid, and the extrusion aid can be sesbania powder. The amount of water, adhesive and extrusion aid added is added according to the actual molding needs, and the present invention has no special requirements. For example, the amount of adhesive added is 0.5wt% to 5wt% of the raw material mass. The amount of extrusion aid added is 0.5wt% to 6wt% of the raw material mass. The amount of water added is 90wt% to 150wt% of the raw material mass.

[0026] According to the present invention, the drying temperature in step (3) is 110-160°C, the drying time is 4-8h, the roasting temperature is 550-650°C, and the roasting time is 4-6h; the inert protective gas can be an inert gas and / or nitrogen, wherein the inert gas is a mixture of one or more of argon and helium.

[0027] According to the present invention, the impregnation solution in step (4) is prepared by first dissolving a nickel source, a phosphorus source and a complexing agent in water, and then dripping a solvent I therein and stirring and mixing. In the impregnation solution, the concentration of nickel is 40 to 120 g / L, the concentration of phosphorus is 10 to 100 g / L, and the concentration of the complexing agent is 20.0 to 200.0 g / L, calculated as nickel oxide. The temperature during the preparation of the impregnation solution is 50 to 100° C., preferably 60 to 90° C., and the time for dripping the solvent I into the solution containing the nickel source, the phosphorus source and the complexing agent is 30 to 180 min, preferably 60 to 120 min.

[0028] According to the present invention, the nickel source in step (4) includes one or more of nickel nitrate, nickel acetate, basic nickel carbonate, and nickel chloride; the phosphorus source includes one or more of phosphoric acid, ammonium monohydrogen phosphate, and ammonium dihydrogen phosphate; and the complexing agent is a compound containing a carboxyl group and / or a carbonyl group, including one or more of citric acid, tartaric acid, malic acid, acetic acid, formic acid, oxalic acid, malonic acid, succinic acid, glucose, fructose, galactose, gluconic acid, and the like.

[0029] According to the present invention, the impregnation in step (5) can be carried out by a spray impregnation method, and a saturated impregnation method or a supersaturated impregnation method can be used during the impregnation.

[0030] According to the present invention, the curing in step (5) is to place the sample after immersion under closed conditions at 10 to 30° C. for 6 to 12 hours, and the curing pressure is not particularly limited and can be autogenous pressure; and / or, the drying condition is drying at 100 to 160° C. for 1 to 8 hours.

[0031] According to the present invention, the composition of the hydrogenation catalyst in step (5), based on the mass of the catalyst and measured by mass fraction, includes:

[0032] Calculated as molybdenum trioxide, the content of Mo is 5.0% to 22.0%.

[0033] Calculated as nickel oxide, the content of Ni is 8.0% to 13.0%.

[0034] Calculated as vanadium pentoxide, the vanadium content is 3% to 10%.

[0035] Calculated as phosphorus pentoxide, the phosphorus content is 0.5% to 4.0%.

[0036] The carbon content is 5.0% to 7.0%.

[0037] The content of complexing agent is 0.5% to 3.0%.

[0038] The content of aluminum oxide is 41.0% to 78.0%.

[0039] According to the present invention, part of the nickel in the catalyst exists in the form of nickel carbide, and the nickel element in the nickel carbide accounts for 30.0wt% to 40.0wt% of the total nickel element.

[0040] According to the present invention, the properties of the catalyst in step (5) are as follows: the specific surface area is 180 to 280 m 2 / g, the pore volume is 0.5-1.3 mL / g, the average pore diameter is 10-15 nm, and the mechanical strength is 130-180 N / cm, preferably 140-180 N / cm.

[0041] Another aspect of the present invention provides a hydrogenation catalyst prepared by the above method. Preferably, the hydrogenation catalyst is a residue oil hydrodesulfurization catalyst or a residue oil hydrodenitrogenation catalyst.

[0042] Compared with the prior art, the present invention has the following advantages:

[0043] 1. In the method of the present invention, by controlling the reaction conditions, the catalyst powder can react with chlorine, and molybdenum can be simply and highly selectively extracted from the catalyst and transferred to the solvent phase. The solvent phase is then added dropwise to a solution containing a nickel source, a phosphorus source and a complexing agent to obtain an impregnation solution. While effectively extracting molybdenum, the carbon deposits in the waste catalyst can be effectively retained in the carrier component. Part of the carbon deposits react with nickel to generate nickel carbide. The carrier component is mixed with an ammonium bicarbonate solution and sealed and heat-treated to obtain an alumina-based carrier. Finally, the impregnation solution is loaded onto the alumina-based carrier, which is beneficial to adjusting the pore structure of the catalyst and increasing the surface area of ​​the carrier. The number of acid sites can produce more coordinated unsaturated sites. On the other hand, it can adjust the loading of active components, especially make molybdenum more evenly loaded on the carrier in the form of +5-valent molybdenum, which is easier to be sulfurized into +4-valent MoS 2 , which accelerates the formation of MoS 2 The rate of the complexing agent is reduced, and the addition of the complexing agent delays the sulfidation of Ni, making it easier to form MoS in the catalyst. 2 The skeleton and the efficient hydrogenation active phase structure of metallic nickel on the outer surface are beneficial to improving the activity and stability of the catalyst.

[0044] 2. The present invention adopts a specific treatment to selectively remove metallic molybdenum from the deactivated hydrogenation catalyst without affecting other active metals loaded on the catalyst. At the same time, the vanadium deposited during the hydrogenation process will form a VS-type active phase after sulfidation, which can maximize the self-catalytic activity of the deposited vanadium.

[0045] 3. The method of the present invention recycles the carrier raw material alumina and carbon deposits in the waste hydrogenation catalyst to prepare a C-containing composite alumina carrier, while recovering the metal in the waste hydrogenation catalyst, reducing the cost of carrier preparation and reducing the harm to the environment. DETAILED DESCRIPTION

[0046] The effects and effects of the present invention are further illustrated below by way of examples, but the following examples do not constitute a limitation of the method of the present invention.

[0047] In the present invention, % refers to mass fraction unless otherwise specified.

[0048] In the present invention, the specific surface area, pore volume and pore distribution are measured by using an ASAP2420 fully automatic physical adsorption instrument from Micromeritics Instruments, Inc., USA. The measurement method is as follows: After the sample is treated at 300°C and 0.1 MPa for 4 h, the liquid N 2 As adsorbent, the adsorption temperature is -196℃, and the analysis test is carried out after accurate weighing. The specific surface area is calculated according to the BET method, and the pore volume and pore distribution are calculated according to the BJH method.

[0049] In the present invention, the catalyst composition is tested by spectrophotometry, and the testing instrument is a Lambda 365 ultraviolet spectrophotometer.

[0050] In the present invention, the composition and properties of the catalyst prepared in each example are shown in Table 1.

[0051] In the present invention, the composition of the spent hydrogenation catalyst used in each example is calculated by mass fraction as follows: 85% of catalyst solids and 15% of petroleum fractions.

[0052] In the present invention, the extraction and deoiling conditions of each example are: the organic solvent is toluene, the extraction temperature is 100°C, the extraction time is 72h, and the mass ratio of the organic solvent to the catalyst is 30:1. The composition of the waste hydrogenation catalyst after extraction and deoiling is calculated by mass fraction:

[0053] 19.2% molybdenum as molybdenum trioxide;

[0054] 8.6% nickel, calculated as nickel oxide;

[0055] 4.2% vanadium as vanadium pentoxide;

[0056] 9.1% Carbon,

[0057] The balance is carrier alumina.

[0058] Example 1

[0059] (1) Take the spent hydrogenation catalyst after industrial operation, extract and remove oil, dry it at 120℃ for 6h, and then crush it into 300 mesh.

[0060] (2) 124 g of catalyst powder was placed in a container, and 3.5 mL / (min·g catalyst) of 98% purity chlorine gas was introduced for reaction at a temperature of 400° C. and a reaction time of 90 min. The catalyst after reaction was cooled to 30° C., then transferred to 434 g of acetone and mixed evenly, and then placed in an ultrasonic generator, with acetone as the medium, and treated at 30° C. and an ultrasonic frequency of 50 KHz for 1 hour, and separated to obtain solvent I and material II, respectively. Among them, material II was 100 g.

[0061] (3) Material II (100 g) prepared in step (2) is placed in 550 g of ammonium bicarbonate solution having a mass concentration of 20.0%. The mixture is transferred into an autoclave and sealed, heated to 100° C. at a rate of 15° C. / min and kept constant at that temperature for 3 hours. The mixture is then heated to 150° C. at a rate of 10° C. / min and kept constant at that temperature for 6 hours. The mixture is then dried at 110° C. for 6 hours. The mixture is then kneaded with 4 g of sesbania powder, 3 g of nitric acid and 120 g of water to form the mixture. The mixture is then dried at 130° C. for 4 hours. The mixture is then calcined at 650° C. in a helium atmosphere for 4 hours to obtain a catalyst carrier A-0.

[0062] (4) Weigh 10.3 g of nickel nitrate hexahydrate, 4.5 g of phosphoric acid, and 6.3 g of tartaric acid, and dissolve them in 60.0 mL of water to obtain a mixed solution. Then, solvent I is added dropwise to the mixed solution for 70 min. The heating temperature is 80° C., the heating time is 4 h, and the obtained solution is recorded as L-0.

[0063] (5) The impregnation solution L-0 was impregnated on the carrier A-0 by spraying to obtain A-1. A-1 was placed in a sealed container at room temperature of 20°C for 6 hours, and then dried at 120°C for 4 hours to obtain CA-1. The composition of catalyst CA-1 is shown in Table 1.

[0064] In the catalyst CA-1, the nickel element in the nickel carbide accounts for 36.0% of the total nickel element, calculated as nickel.

[0065] Example 2

[0066] (1) Take the spent hydrogenation catalyst after industrial operation, extract and remove oil, dry it at 140°C for 4 hours, and then crush it into 400 mesh.

[0067] (2) 124 g of catalyst powder was placed in a container, and 4.9 mL / (min·g catalyst) of 97% purity chlorine gas was introduced for reaction at a temperature of 400° C. and a reaction time of 65 min. The reacted catalyst was cooled to 30° C., then transferred to 500 g of acetone and mixed evenly, and then placed in an ultrasonic generator, with acetone as the medium, and treated at 60° C. and an ultrasonic frequency of 100 KHz for 0.5 hours, and separated to obtain solvent I and material II, respectively. Among them, material II was 100 g.

[0068] (3) Material II (100 g) prepared in step (2) is placed in 450 g of ammonium bicarbonate solution having a mass concentration of 17.5%. The mixture is transferred into an autoclave and sealed, heated to 100° C. at a rate of 10° C. / min and kept constant at that temperature for 3 hours. The mixture is then heated to 160° C. at a rate of 7° C. / min and kept constant at that temperature for 5 hours. The mixture is then dried at 120° C. for 5 hours. The mixture is then kneaded with 5 g of sesbania powder, 4 g of nitric acid and 115 g of water, dried at 120° C. for 5 hours and calcined at 650° C. in a helium atmosphere for 4 hours to obtain a catalyst carrier B-0.

[0069] (4) Weigh 10.3 g of nickel nitrate hexahydrate, 5.39 g of phosphoric acid, and 4.16 g of tartaric acid, and dissolve them in 60.0 mL of water to obtain a mixed solution. Then, solvent I is added dropwise to the mixed solution for 120 min. The heating temperature is 80° C., the heating time is 4 h, and the obtained solution is recorded as L-0.

[0070] (5) The impregnation solution L-0 was impregnated on the carrier B-0 by spraying to obtain B-1. B-1 was placed in a closed container at room temperature 25°C for 6 hours and then dried at 110°C for 5 hours to obtain CB-1. The composition of catalyst CB-1 is shown in Table 1.

[0071] In the catalyst CB-1, the nickel element in the nickel carbide accounts for 37.9% of the total nickel element, calculated as nickel.

[0072] Example 3

[0073] (1) Take the spent hydrogenation catalyst after industrial operation, extract and remove oil, dry it at 160°C for 3 hours, and then crush it into 400 mesh.

[0074] (2) 124 g of catalyst powder was placed in a container, and 5.3 mL / (min·g catalyst) of 98% purity chlorine gas was introduced for reaction at a reaction temperature of 350° C. and a reaction time of 60 min. The catalyst after the reaction was cooled to 25° C., then transferred to 400 g of tetrahydrofuran, mixed evenly, and placed in an ultrasonic generator, using tetrahydrofuran as a medium, and treated at 30° C. and an ultrasonic frequency of 100 KHz for 1 hour, and separated to obtain solvent I and material II, respectively. Among them, material II was 100 g.

[0075] (3) Material II (100 g) prepared in step (2) is placed in 600 g of ammonium bicarbonate solution having a mass concentration of 25%. The mixture is transferred into an autoclave and sealed, and the temperature is increased to 90° C. at a rate of 15° C. / min and kept constant for 3 hours. The temperature is then increased to 150° C. at a rate of 10° C. / min and kept constant for 6 hours. The mixture is then dried at 120° C. for 5 hours. The mixture is then kneaded with 3 g of sesbania powder, 4 g of nitric acid and 100 g of water, and the mixture is dried at 120° C. for 4 hours. The mixture is then calcined at 630° C. in a helium atmosphere for 5 hours to obtain a catalyst carrier C-0.

[0076] (4) Weigh 10.3 g of nickel nitrate hexahydrate, 5.9 g of phosphoric acid, and 8.0 g of tartaric acid, and dissolve them in 60.0 mL of water to obtain a mixed solution. Then, solvent I is added dropwise to the mixed solution for 90 min. The heating temperature is 60° C., the heating time is 5 h, and the obtained solution is recorded as L-0.

[0077] (5) The impregnation solution L-0 was impregnated on the carrier C-0 by spraying to obtain C-1. C-1 was placed in a closed container at room temperature 25°C for 6 hours and then dried at 120°C for 4 hours to obtain CC-1. The composition of catalyst CC-1 is shown in Table 1.

[0078] In the catalyst CC-1, the nickel element in the nickel carbide accounts for 35.5% of the total nickel element, calculated as nickel.

[0079] Example 4

[0080] (1) Take the spent hydrogenation catalyst after industrial operation, extract and remove oil, dry it at 160℃ for 4h, and then crush it into 500 mesh.

[0081] (2) 124 g of catalyst powder was placed in a container, and 3.9 mL / (min·g catalyst) of 99% purity chlorine gas was introduced for reaction at a reaction temperature of 300° C. and a reaction time of 80 min. The catalyst after the reaction was cooled to 30° C., then transferred to 500 g of acetic acid, mixed evenly, and placed in an ultrasonic generator, with acetic acid as the medium, at 70° C. and an ultrasonic frequency of 50 KHz for 2 hours, and separated to obtain solvent I and material II, respectively. Among them, material II was 100 g.

[0082] (3) Material II (100 g) prepared in step (2) is placed in 550 g of ammonium bicarbonate solution having a mass concentration of 20.0%. The mixture is transferred into an autoclave and sealed, heated to 100° C. at a rate of 14° C. / min and kept constant at that temperature for 3 hours. The mixture is then heated to 160° C. at a rate of 9° C. / min and kept constant at that temperature for 6 hours. The mixture is then dried at 110° C. for 6 hours. The mixture is then kneaded with 4 g of sesbania powder, 3 g of nitric acid and 120 g of water, dried at 130° C. for 4 hours and calcined at 600° C. in a helium atmosphere for 4 hours to obtain a catalyst carrier D-0.

[0083] (4) Weigh 10.3 g of nickel nitrate hexahydrate, 4.5 g of phosphoric acid, and 6.3 g of tartaric acid, and dissolve them in 60.0 mL of water to obtain a mixed solution. Then, solvent I is added dropwise to the mixed solution for 60 min. The heating temperature is 80° C., the heating time is 4 h, and the obtained solution is recorded as L-0.

[0084] (5) The impregnation solution L-0 was impregnated on the carrier D-0 by spraying to obtain D-1. D-1 was placed in a sealed container at room temperature 20°C for 6 hours and then dried at 120°C for 4 hours to obtain CD-1. The composition of catalyst CD-1 is shown in Table 1.

[0085] In the catalyst CD-1, the nickel element in the nickel carbide accounts for 36.1% of the total nickel element, calculated as nickel.

[0086] Comparative Example 1

[0087] Compared with Example 1, only the chlorine gas in step (2) is replaced by air. The other steps are the same as in Example 1.

[0088] A comparative hydrogenation catalyst DCA-1 was prepared.

[0089] In the catalyst DCA-1, the nickel element in the nickel carbide accounts for 10.1% of the total nickel element.

[0090] Comparative Example 2

[0091] Compared with Example 1, a fresh catalyst before deactivation was used as a comparison to prepare a comparative hydrogenation catalyst DCA-2.

[0092] Comparative Example 3

[0093] Compared with Example 1, the comparison hydrogenation catalyst DCA-3 was prepared by directly preparing the carrier by omitting the ammonium bicarbonate heat treatment step.

[0094] In the catalyst DCA-3, the nickel element in the nickel carbide accounts for 34.8% of the total nickel element.

[0095] Comparative Example 4

[0096] Compared with Example 1, no complexing agent was added during the preparation of the impregnation solution to prepare a comparative hydrogenation catalyst DCA-4.

[0097] In the catalyst DCA-4, the nickel element in the nickel carbide accounts for 34.4% of the total nickel element.

[0098] Table 1 Composition of the catalyst obtained in each example

[0099]

[0100] Table 2 Properties of the catalysts obtained in each example

[0101]

[0102] Catalyst evaluation

[0103] The catalysts obtained in the examples and comparative examples were evaluated using the feedstock oils listed in Table 3. The reaction conditions are shown in Table 3, and the evaluation results are shown in Table 4.

[0104] Table 3 Raw oil properties and reaction conditions

[0105] project nature Raw oil properties <![CDATA[Density / kg·m -3 > 970.0 S / wt% 2.2 N / wt% 0.54 <![CDATA[Ni+V / μg·g -1 ]]> 72 Reaction conditions Reaction temperature / ℃ 350 Pressure / MPa 7.5 <![CDATA[Liquid hourly space velocity / h -1 > 0.5 Hydrogen to oil volume ratio 550

[0106] Table 4 Evaluation results of catalysts of various examples

[0107] Removal rate Operation time, h Example 1 Example 2 Example 3 Example 4 HDS, % 200 98.3 98.1 98.6 98.1 HDS, % 2000 86.6 88.8 86.4 87.5 HDN, % 200 94.2 91.5 92.3 93.4 HDN, % 2000 81.4 82.4 83.1 82.8

[0108] Table 4

[0109] Removal rate Operation time, h Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 HDS, % 200 61.4 98.2 62.4 65.4 HDS, % 2000 42.8 86.6 45.1 47.1 HDN, % 200 54.5 91.7 54.3 55.6 HDN, % 2000 30.2 81.6 31.1 32.5

[0110] The above describes the specific implementation of the present invention in detail, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the various technical features being combined in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for recycling a spent hydrogenation catalyst, comprising the following steps: (1) crushing the solid after extracting and removing oil from the molybdenum-nickel waste catalyst; (2) After the catalyst powder reacts with chlorine, it is cooled and transferred to an anhydrous organic solvent for ultrasonic treatment to separate solvent I and material II; (3) mixing material II with an ammonium bicarbonate solution and subjecting the mixture to sealed heat treatment, forming the treated material, drying it, and calcining it in an inert gas atmosphere to obtain an alumina-based carrier; (4) adding solvent I dropwise to a solution containing a nickel source, a phosphorus source and a complexing agent to obtain an impregnation solution; (5) The impregnation solution obtained in step (4) is impregnated into an alumina-based carrier, and then cured and dried to obtain a hydrogenation catalyst.

2. The method according to claim 1, characterized in that: The flow rate of chlorine gas in step (2) is 2.7 to 6.8 mL / (min·g catalyst); And / or, the reaction conditions are as follows: the reaction temperature is 300-400° C., and the reaction time is 40-90 min.

3. The method according to claim 1, characterized in that: The ultrasonic frequency in step (2) is 10KHz to 150KHz, the ultrasonic treatment temperature is 20°C to 70°C, and the treatment time is 0.5 to 2h.

4. The method according to claim 1, characterized in that: The mass ratio of material II to the ammonium bicarbonate solution in step (3) is 1:4 to 1:7, and the mass concentration of the ammonium bicarbonate solution is 15% to 25%.

5. The method according to claim 1, characterized in that: The sealing heat treatment temperature in step (3) is 120-160° C., and the treatment time is 4-8 hours.

6. The method according to claim 1, characterized in that: In step (3), sealing pretreatment is performed before the sealing heat treatment, the pretreatment temperature is 60 to 100° C., and the constant temperature treatment time is 2 to 4 hours; And / or, the heating rate before pretreatment is 10-20°C / min, and the heating rate after pretreatment is 5-10°C / min, and the heating rate after pretreatment is at least 3°C / min lower than that before pretreatment, preferably at least 5°C / min lower.

7. The method according to claim 1, characterized in that: The drying temperature in step (3) is 110-160° C., and the drying time is 4-8 hours; and / or the roasting temperature is 550-650° C., and the roasting time is 4-6 hours.

8. The method according to claim 1, characterized in that: In the impregnation solution of step (4), the concentration of nickel, calculated as nickel oxide, is 40 to 120 g / L, the concentration of phosphorus is 10 to 100 g / L, and the concentration of the complexing agent is 20.0 to 200.0 g / L; And / or, the time for adding the solvent I dropwise to the solution containing the nickel source, the phosphorus source and the complexing agent is 30 to 180 minutes, preferably 60 to 120 minutes.

9. The method according to claim 1, characterized in that: The complexing agent described in step (4) is a compound containing a carboxyl group and / or a carbonyl group, including one or more of citric acid, tartaric acid, malic acid, acetic acid, formic acid, oxalic acid, malonic acid, succinic acid, glucose, fructose, galactose, and gluconic acid.

10. The method according to claim 1, characterized in that: The curing in step (5) is to place the sample after immersion under closed conditions at 10-30° C. for 6-12 hours; and / or, the drying conditions are to dry at 100-160° C. for 1-8 hours.

11. The method according to claim 1, characterized in that: The composition of the hydrogenation catalyst in step (5), based on the mass of the catalyst and measured by mass fraction, includes: Calculated as molybdenum trioxide, the content of Mo is 5.0% to 22.0%. Calculated as nickel oxide, the content of Ni is 8.0% to 13.0%. Calculated as vanadium pentoxide, the vanadium content is 3% to 10%. Calculated as phosphorus pentoxide, the phosphorus content is 0.5% to 4.0%. The carbon content is 5.0% to 7.0%. The content of complexing agent is 0.5% to 3.0%. The content of aluminum oxide is 41.0% to 78.0%.

12. The method according to any one of claims 1 to 11, characterized in that: In the hydrogenation catalyst described in step (5), part of the nickel exists in the form of nickel carbide, and the nickel element in the nickel carbide accounts for 30.0wt% to 40.0wt% of the total nickel element.

13. The method according to claim 1, characterized in that: The properties of the catalyst in step (5) are as follows: the specific surface area is 180 to 280 m 2 / g; and / or, a pore volume of 0.5 to 1.3 mL / g; and / or, an average pore diameter of 10 to 15 nm; and / or, a mechanical strength of 130 to 180 N / cm.

14. The hydrogenation catalyst prepared by the method of any one of claims 1 to 13, wherein the hydrogenation catalyst is preferably a residue oil hydrodesulfurization catalyst or a residue oil hydrodenitrogenation catalyst.

Citation Information

Patent Citations

  • Preparation method for loaded iron-based catalyst

    CN105709791A

  • Method for recycling waste hydrogenation catalyst

    CN105709853A

  • Method for preparing hydrotreating catalyst by impregnating method

    CN106807419A

  • Method for recycling hydrogenation catalyst waste

    CN108067242A

  • Recycling method of hydrotreating catalyst

    CN108067245A